2013
DOI: 10.1021/mp300569j
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding DNA in Lipofection of HeLa Cells—A Few Insights

Abstract: In cationic carrier-mediated gene delivery, the disproportional relationship between the quantity of delivered DNA and the amount of encoded protein produced is a well-known phenomenon. The numerous intracellular barriers which need to be overcome by pDNA to reach the nucleoplasm play a major role in it. In contrast to what one would expect, a partial replacement of coding pDNA by noncoding DNA does not lead to a decrease in transfection efficiency. The mechanism underlying this observation is still unclear. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Currently, cells are challenged with an excessive amount of pDNA to reach in vitro gene delivery. We and others, however, found that more than 90% of the originally administered pDNA can be replaced by noncoding pDNA, demonstrating the enormous potential to further optimize pDNA delivery and decrease the dose applied to cells [21,22]. In this research paper, we evaluated two strategies to increase the fraction of initially applied pDNA that reaches the nuclear interior of the cells.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, cells are challenged with an excessive amount of pDNA to reach in vitro gene delivery. We and others, however, found that more than 90% of the originally administered pDNA can be replaced by noncoding pDNA, demonstrating the enormous potential to further optimize pDNA delivery and decrease the dose applied to cells [21,22]. In this research paper, we evaluated two strategies to increase the fraction of initially applied pDNA that reaches the nuclear interior of the cells.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, in cases of pDNA/PEI/CS and pDNA/PEI/CS‐CHO nanoplexes, the transfection efficiency markedly diminished and became nearly identical to that of pDNA/PEI‐based transfection experiment (Figure B). This demonstrates that controlled release of the nanoplexes from endolysosomal compartments is critical for improving transfection efficiency as the half‐life of pDNA in the cytosol rarely exceeds 90 min …”
Section: Resultsmentioning
confidence: 97%
“…Cationic polymer such as PEI can favor endosomal escape by “proton sponge effect” initiating the swelling of the endosomes . Recently, Symens et al reported that prolonged release of coding pDNA from nanoplexes by diluting the pDNA with noncoding DNA could favor transfection efficiency . Thus, tuning endosomal release of pDNA could have significant implication on transfection efficiency as this could prevent premature degradation of the DNA in cytosol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the observed plateau that occurs for the shape parameter in the transfection concentration series (Fig. 4) may be indicative of a saturation effect on one or more of the mechanisms that mediate DNA delivery, e.g., escape from the endosomes, cytoplasmic concentration during mitosis, or nuclear shuttling activities 5,7,[9][10][11][12][13] . Alternatively, it might reflect a transition in the dominating source of noise, where stochastic expression effects begins to dominate over gene-delivery variance.…”
Section: Discussionmentioning
confidence: 99%